Drive for commercial desertification in mountain areas: Evidence from the province of Sondrio (Italy), 2010−2022 - Clerici, Maria Antonietta (Quaestiones Geographicae, 2024)
The availability of an adequate network of services of general interest (SGI) is a major issue for the vitality of rural areas, which is very much on the political agendas of different governmental levels. This is also true for the narrow field of food retailing, which is the subject of this paper. Here we focus on the provision of commercial services in the province of Sondrio, a small stretch of land in the Alps on the border between Italy and Switzerland. This paper investigates the rearrangement of the provincial distribution system between 2010 and 2022, focusing on the dynamics of food retail density in terms of shops and available floor area with respect to the resident population. What emerges is a progressive commercial rarefaction that plays a role in reshaping the relationship between the populations of built- up areas at different altitudes and leads to a sharp increase in instances of under-provision and commercial desertification in the strict sense. The way these critical situations affect the different municipalities depends on their individual position within their settlement networks, with residential municipalities being the most affected, even though they are not necessarily isolated or in remote locations. Retail dynamics in disadvantaged rural mountain areas must not be underestimated, as it also contributes to territorial cohesion.